FLUKTUASI EKPOR NONMIGAS INDONESIA PASCA KERJA SAMA INDONESIA-KOREA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT TAHUN 2021-2023 - Warni, Khofifah; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The Indonesia–Korea Comprehensive Economic Partnership Agreement (IK-CEPA) signed in 2020 and implemented in 2021, was expected to boost Indonesia’s non-oil and gas export performance to South Korea through tariff elimination and improved market access. However, data from 2021 to 2023 show that Indonesia’s non-oil and gas exports experienced significant fluctuations despite the agreement. This study aims to examine the causes of these fluctuations in the post-IK-CEPA period. Using a descriptive qualitative method, this research relies on secondary data obtained from Statistics Indonesia (BPS), the Ministry of Trade, and relevant international institutions. The analysis focuses on the value and volume of Indonesia’s non-oil and gas exports to South Korea during the 2021–2023 period. The study is framed within the theory of international cooperation and the liberalism perspective to better understand trade dynamics. The results reveal that the IK-CEPA agreement alone has not been sufficient to ensure export stability in the absence of supportive global economic conditions. External factors such as the COVID-19 pandemic and geopolitical tensions played a significant role in disrupting export flows. Although IK-CEPA offers important opportunities, realizing its full potential requires strategic policy improvements, product competitiveness, and market diversification to strengthen Indonesia’s position in the global trade environment. Keywords: non-oil and gas exports, IK-CEPA, international trade, export fluctuations, Indonesia–Korea relations.